Symbolism in perfume advertising: myths, archetypes and colours. The case of MY WAY by Giorgio Armani. - Tolonen Torralbo, Marta (2024)
Advertising is a powerful tool for product promotion. As the use of perfumes is in its nature symbolic, meaning that their consumption does not stem from basic needs but from higher level needs such as the Love-, Esteem-, and Self-actualization- needs (Maslow, 1987, pp. 15-22), when promoting hedonic products practitioners must develop creative techniques to connect to their consumers on a deeper level. For this reason, advertisers take into consideration the power of consumers’ individual and group identity to connect to their audience, triggering in them affective responses and connections with their products (Ganassali & Matysiewicz, 2021). The cosmetics industry relies greatly on building strong and aspirational brand narratives to represent their products, leading consumers to interpret those stories, and consume the meanings behind those products (Ketteman, 2014, pp. 45, 47), leading consumers to construct their identities through consumption (Rokka & Ulver, 2023, p. 17). To build advertising scenarios where the target audience feels represented, and the essence of the perfume is communicated, advertisers include signs and symbols, archetypal characters and allude to ancient myths in their narrative communication. This study aims to analyse the communication and targeting strategy of Giorgio Armani’s MY WAY perfume advertisement as a means to gain deeper knowledge on the impact that non-verbal communication has in the persuasive effect of hedonic product advertisement. The chosen research method is Roland Barthe’s Mythological system of semiotic analysis, a qualitative research method, taken on from an inductive and iterative approach. The results of the study point that the use of ancient myths, archetypal characters and colour symbology play a crucial role in the communication of character and product identity and the creation of meaning of the MY WAY perfume.